Strategi Peningkatan Kualitas Roti Tawar di PT. Indoroti Prima Cemerlang Cabang Bali - Sianturi, Greace Tesalonika; Satriawan, I Ketut; Anom Yuariani, Dewa Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 1 (2023): MaretDO - 10.24843/JRMA.2023.v11.i01.p15, 2023)
Bread is one of the most popular foods. Bread consists of two types, namely white bread and sweet bread. PT Indoroti Prima Cemerlang Bali Branch is a company engaged in the bakery industry. Thicker white bread is one of the products of PT Indoroti Prima Cemerlang Bali Branch which is the focus of increasing sales. Therefore, this study aims to determine the attributes of thicker white bread that can satisfy consumer needs and provide solutions for improvement. Sampling was done by purposive sampling method and data collection was done by distributing questionnaires directly to respondents and observation. The analysis was carried out using the quality function deployment (QFD) method. The results obtained in this study are that there are 8 attributes that are considered very important by consumers, namely expiration, food safety, texture, price, taste, standard shape, color and aroma with the highest satisfaction value of the expiration date attribute (5.00) and the lowest texture attribute (4.29). The strategy to improve product quality is to prioritize improvements to the attributes of texture, taste, standard shape, color, and aroma. The priority for improving technical parameters is combustion, preparation of raw materials and second mixing.